Is there a relationship between serum vitamin D levels and onychomycosis? - Zuhal Metin; Koray Durmaz (Galenos Publishing House, 2023)
Background and Design: Vitamins are necessary for various biochemical functions and are either insufficiently synthesized or not synthesized by the organism; therefore, they are taken from the diet. Many dermatoses such as psoriasis, atopic dermatitis, rosacea, acne vulgaris, vitiligo, and pityriasis versicolor, which are associated with vitamin D deficiency, have been reported. This cross-sectional study aimed to compare vitamin D levels between patients with onychomycosis and healthy controls and determine the relationship between vitamin D and onychomycosis. Materials and Methods: Serum 25-hydroxyvitamin D [25(OH)D] levels were measured in the blood sample for any reason in the last 1 month of patients diagnosed with onychomycosis and healthy controls. Results: The study included 40 participants (21 men). The mean level of serum 25(OH)D of all participants was 12.66 ng/mL. No significant correlation was found between the age of the participants and 25(OH)D levels. 25(OH)D levels were lower in the patient group (10.79+-8.12 ng/mL) than in the control group (13.91+-6.76 ng/mL) (p=0.02). Conclusion: The results of this study revealed that vitamin D levels are low in the Turkish population, but mean values are lower in patients with onychomycosis.